DAMPAK PANDEMI COVID- 19 TERHADAP PENERIMAAN PAJAK DI INDONESIA - Situmorang, Dokman Marulitua; Wahyudi, Wahyudi (Journal Accounting International Mount Hope, 2023)
Based on these problems, the research is intended to analyze the relationship between. TheCovid-19 pandemic caused a decline in tax revenues in Indonesia which also caused economicgrowth to decline. The data collection technique used is quantitative data collection in the form oftax revenues in Indonesia for 2018 - 2020 obtained from the Information System within theDirectorate General of Taxes. Data collection for that year was based on the consideration thatthe periods before and during the Covid-19 pandemic had to be compared to obtain researchconclusions. Based on the data obtained, it is then analyzed to link the facts with variousapplicable regulations so that we can get an idea of the influence of the Covid-19 pandemic ontax revenues in Indonesia. The research results show that the Covid-19 pandemic in Indonesiahas had a significant effect on tax revenues. The government has taken various measures tominimize the decline in tax revenues, which of course cannot be avoided. As is known, taxrevenues will be managed to fund the handling of Covid-19 in Indonesia, so we should help withthe government's steps in the easiest way to do this, namely by purchasing goods from MSMEbusiness actors so that the economy in Indonesia can improve.